Pengaruh Literasi Keuangan, Sikap Keuangan, Perilaku Keuangan Terhadap Kinerja UMKM Kota Bengkulu - Adristi Aprila Utami; Abdullah Abdullah (Journal of Economic, Bussines and Accounting (COSTING), 2024)
The purpose of this research is to evaluate how financial literacy, financial attitudes, and financial behavior impact the performance of micro, small, and medium enterprises (MSMEs) in the city of Bengkulu. This study involved 100 MSMEs selected using the Slovin method, and data were collected directly by the researcher through the completion of questionnaires by respondents. The results of the t-test indicate that financial literacy has a significant impact on the performance of MSMEs in the city of Bengkulu, while financial attitudes and behavior do not have a significant impact on the performance of MSMEs. This research can assist the research subjects in addressing and overcoming issues in business management and optimizing business performance. Keywords: Financial literacy, Financial attitude, Financial behavior